Progress on open cathode proton exchange membrane fuel cell: Performance, designs, challenges and future directions - Kurnia, J.C. (Elsevier Ltd, 2021)
Fuel cell is considered as a promising candidate to replace internal combustion engine in the future vehicles amid growing interest to lessen environment degradation due to fossil fuel burning. To achieve successful adoption of fuel cell-based power train, a simple and reliable fuel cell system is required. Open cathode fuel cell is one of such systems which offers simple configuration where the ambient air is used directly to provide cooling and serve as an oxidant, thus eliminating the requirement for a complex air supply subsystem, minimizing parasitic load and reducing overall cost of the system. The major challenge with the open cathode configuration is the strong dependence of the stack performance on the ambient conditions. To address this issue, numerous studies evaluating the performance of open cathode fuel cell and various factors affecting it have been conducted and reported. Important findings from these studies are currently scattered, impeding the pace of research and development. To assist and expedite further research and development of open cathode fuel cell and accelerate its mass application, it is imperative to extract and discuss the important findings of previous studies and identify the gap that requires further attention. This paper presents a comprehensive review of the current development of open cathode fuel cell and identifies various aspects that can potentially influence its future advancements. In addition, the research and development needs for further growth of the field are highlighted and discussed. Â© 2020